Analysis of Employee Career Development Strategies Based on Gamification and Microlearning in Enhancing Retention and HR Performance - Azzaakiyyah, Hizbul Khootimah; Junaidi, Ahmad (ADMAN: Journal of Contemporary Administration and Management, 2025)
This study aims to analyze employee career development strategies based on gamification and microlearning and their impact on human resource (HR) retention and performance. The research employs a qualitative approach with a literature review method, using descriptive analysis of literature obtained from Google Scholar and credible websites between 1964 and 2025. Initially, 50 articles were collected, then rigorously screened to obtain 24 relevant articles for analysis. The review findings indicate that gamification enhances motivation, engagement, and enjoyable learning experiences, while microlearning facilitates short, focused, and applicable learning. The integration of both creates adaptive and personalized career development experiences, contributing to improved employee retention and HR performance. This study provides practical implications for organizations in designing technology-based career development strategies while reinforcing the theoretical foundations of Human Capital and Self-Determination Theory in the context of modern HR development.